Can We Afford to Exclude Patients Throughout Health Technology Assessment? - Wale, Janet L.; Chandler, David; Collyar, Deborah; Hamerlijnck, Dominique; Saldana, Roberto; Pemberton-Whitely, Zack (Frontiers in Medical Technology, 2022)
Health technology assessment (HTA) is intended to determine the value of health technologies and, once a technology is recommended for funding, bridge clinical research and clinical practice. Understanding the values and beliefs expressed by patients and health professionals can help guide this knowledge transfer and work toward managing the expectations of end users. We gathered patient and patient group leader experiences to gain insights into the roles that patients and patient advocacy groups are playing. We argue that through partnerships and co-creation between HTA professionals, researchers and patient advocates we can strengthen the HTA process and better align with service delivery where person-centered care and shared decision making are key elements. Patient experiences and knowledge are important to the democratization of evidence and the legitimacy of HTAs. Patient preference studies are used to balance benefits with potential harms of technologies, and patient-reported outcomes (PROs) can measure what matters to patients over time. A change in culture in HTA bodies is occurring and with further transformative thinking patients can be involved in every step of the HTA process. Patients have a right to be involved in HTAs, with patients’ values central to HTA deliberations on a technology and where patients can provide valuable insights to inform HTA decision-making; and in ensuring HTA methodologies evolve. By evaluating the implementation of HTA recommendations we can determine how HTA benefit patients and their communities. Our shared commitment can positively effect the common good and provide benefits to individual patients and their communities.